Evidence for Mild Diagenesis in Archaeological Human Bones from the Fewet Necropolis (SW Libya): New Insights and Implications from ATR–FTIR Spectroscopy - Francesca Castorina; Umberto Masi; Elisabetta Giorgini; Lucia Mori; Mary Anne Tafuri; Valentina Notarstefano (Applied Sciences, 2023)
Bones offer a great amount of information on ancient populations regarding both their lifestyle habits and the influence of the living area. Bones are composed by an inorganic component, i.e., carbonated hydroxyapatite (Ca10[(PO4)6−x(CO3)x](OH)2), and an organic matrix (mainly proteins and collagen). After death, bones are subjected to diagenetic processes, with changes in structure, morphology, and chemical composition. All these modifications strictly depend on several factors, including the nearby environment, the climate, and the burial modality. Hence, a precise knowledge of the diagenetic processes affecting bones after death is mandatory. In this study, archeological human bones from the Garamantian necropolis of Fewet (Libyan Sahara) were analyzed by ATR–FTIR spectroscopy to elucidate the role of the burial location and modality, as well as the highly arid environment in the diagenesis rate. Several spectral parameters related to structural and chemical features of the organic and mineral components (i.e., AmideI/PO4, C/P, MM, FWHM603, and IRSF indexes) were statistically analyzed. Spectral data were compared with those from modern ruminants from the same site to evaluate a possible time-dependent correlation between the chemical composition and the diagenetic processes. A mild diagenesis was found in all human bones, even though it had a variable degree depending on the burial location.